Fostering a link between creativity and consumer acceptance: essential factors for advancing innovations in food industry - Grinberga-Zalite, Gunta; Zvirbule, Andra; Hernik, Joanna (Creativity Studies, 2024)
This research aims to explore the acceptance of unconventional food products that convey creative solutions for sustainable food production and consumption. This paper presents the first stage results of an extensive Baltic Sea region’s population survey organized to understand how innovative food products’ creators could better enhance the link between sustainable products and different segments’ customer acceptance. In scope of this study, the authors focused on youth market segments, who are known for their adventurous and experimental eating habits. The authors hypothesized that products that have been created to comply with socially responsible and sustainable food products’ requirements face resistance from the youth who do not view them as superior to conventional ones. The cross-sectional study utilized mixed-method methodology, combining qualitative and quantitative approaches, including a literature review, in-depth focus group interviews, and comparative analysis using normal distribution assessment and sentiment classification. The research findings indicate that while the youth acknowledge the social and environmental benefits of innovative food products, they remain hesitant to adopt them personally. Therefore, it is vital for innovative food creators to understand the biases and behaviors of young consumers, ensuring transparency about product contents, motivating them to embrace new consumption models, try unconventional foods, and highlight the personal and societal advantages of purchasing these items.